Increasing stringent regional environmental regulations impact gasoline demand in China. (February 2019) - Li, Zhe; Sun, Renjin; Dong, Kangyin; Chung, Keng H.
Abstract: Forecasting of the gasoline demand is a key issue for refineries in China. Some international energy organizations (IEOs) and international oil companies have estimated the gasoline demand in China for the next 20 years. These organizations and companies used the assumptions that the technology of clean-energy vehicles do not gain significant progresses, and they do not consider the trends of policy changes of different provinces in China. So the forecast of IEOs (international energy organizations) may not reflect the real trend of gasoline demand in China. In this paper, we considered more stringent regional environmental regulations and the possibility of technological progress in clean-energy vehicles, using the bottom to up method to estimate the gasoline demand of all 30 provinces in China, adding them up, to gain the forecast of total gasoline demand in China for the next twenty years. The result shows that gasoline demand will increase slower and decrease faster than the estimation of some mean IEOs (international energy organizations).